Discovery of novel ayurvedic formulation for the treatment of vitiligo - Pandey, Ravi S (Asian Journal of Medical Sciences, 2014)
DOI: http://dx.doi.org/10.3126/ajms.v6i1.10805 Asian Journal of Medical Sciences Vol.6(1) 2015 132-133